Análise da estrutura genérica das instruções na fala do professor de inglês: contribuições para o teste oral do Epple - Andrelino, Paulo José [UNESP] (2014)
This research study approaches one of the aspects of language assessment of foreign language teacher's language competence, more precisely his/her oral proficiency. The background for the investigation consists of a partial study of the target language use domain of the foreign language teacher profession as a basis for devising and evaluate tasks for the oral test of EPPLE (Exame de Proficiência para Professores de Língua Estrangeira). Our investigation is based on the generic structure characterization of teachers' oral instructions that are present in their speech when they organize the activities of language practice in classes of English as a foreign language. In order to make this characterization feasible we used the Systemic Functional Linguistics, and we based our data analysis upon Martin's work on textual genres (1985, 1991, 1997, 1999,2009), and on the work of Hasan (1977, 1989, 1996) on the Generic Structure Potential (GSP). As for the research methodology we used an interpretive approach (ERICSON, 1986), and recorded, in audio and video, the classes of three teacher-educators, as well as the mini classes of the student-teachers of two of these teacher-educators. Our research study approaches both quantitative and qualitative aspects of the data. We analyzed 103 texts and the results allowed us to devise a GSP of the foreign language teachers' oral instructions. We identified one obligatory move and six optional moves within the GSP, as well as a partial order among these elements. The GSP may be divided into three blocks. The first one is made up of three moves in a fixed order. The second block contains three more moves. The order of these three moves may be reversible within the block. The last block is constituted of one move, considered the closing element of the instructional text. The results may be used as parameters for various actions within the Applied Linguistics ...